Prove that $\dfrac{{\tan \theta }}{{\left( {1 - \cot \theta } \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}} = 1 + \tan \theta + \cot \theta = \sec \theta \times \csc \theta + 1$.
Answer
Verified
509.4k+ views
Hint – In this question we have to prove that the left hand side of the given expression is equal to the right hand side. Use the trigonometric identities and algebraic formula like\[\cot \theta = \dfrac{1}{{\tan \theta }}\],\[\left[ {{\text{ta}}{{\text{n}}^2}\theta + 1 = {{\sec }^2}\theta } \right]\], $\left( {{a^3} - {b^3}} \right) = \left( {a - b} \right)\left( {{a^2} + {b^2} + ab} \right)$to simplify the L.H.S part and prove it equal to the R.H.S part.
Complete step by step solution:
Given equation is
$\dfrac{{\tan \theta }}{{\left( {1 - \cot \theta } \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}} = 1 + \tan \theta + \cot \theta = \sec \theta \times \csc \theta + 1$
Consider L.H.S
$ \Rightarrow \dfrac{{\tan \theta }}{{\left( {1 - \cot \theta } \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}$
Now as we know \[\cot \theta = \dfrac{1}{{\tan \theta }}\] so, substitute this value in above equation we have,
\[\dfrac{{\tan \theta }}{{\left( {1 - \dfrac{1}{{\tan \theta }}} \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}\]
Now simplify the above equation we have,
\[ \Rightarrow \dfrac{{{{\tan }^2}\theta }}{{\left( {\tan \theta - 1} \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}\]
\[ \Rightarrow \dfrac{{{{\tan }^2}\theta }}{{\left( {\tan \theta - 1} \right)}} - \dfrac{{\cot \theta }}{{\left( {\tan \theta - 1} \right)}} = \dfrac{{{{\tan }^2}\theta - \dfrac{1}{{\tan \theta }}}}{{\tan \theta - 1}} = \dfrac{{{{\tan }^3}\theta - 1}}{{\tan \theta \left( {\tan \theta - 1} \right)}}\]
Now as we know $\left( {{a^3} - {b^3}} \right) = \left( {a - b} \right)\left( {{a^2} + {b^2} + ab} \right)$ so, use this property in above equation we have,
\[ \Rightarrow \dfrac{{\left( {\tan \theta - 1} \right)\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta \left( {\tan \theta - 1} \right)}} = \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }}\]
Now divide by $\tan \theta $ in above equation we have,
\[ \Rightarrow \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }} = 1 + \tan \theta + \cot \theta \]
= R.H.S
Now we have to again prove that
$1 + \tan \theta + \cot \theta = \sec \theta \times \csc \theta + 1$
Now consider L.H.S
\[ \Rightarrow 1 + \tan \theta + \cot \theta \]
\[ \Rightarrow 1 + \tan \theta + \cot \theta = \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }}\] (From above equation)
Now as we know that \[\left[ {{\text{ta}}{{\text{n}}^2}\theta + 1 = {{\sec }^2}\theta } \right]\] so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{{{{\sec }^2}\theta + \tan \theta }}{{\tan \theta }} = \dfrac{{{{\sec }^2}\theta }}{{\tan \theta }} + 1\]
Now we know that \[{\text{sec}}\theta {\text{ = }}\dfrac{1}{{\cos \theta }},{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}\] so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{{{{\sec }^2}\theta }}{{\tan \theta }} + 1 = \dfrac{{\cos \theta }}{{{{\cos }^2}\theta \times \sin \theta }} + 1 = \dfrac{1}{{\cos \theta \times \sin \theta }} + 1\]
Now we know $\dfrac{1}{{\sin \theta }} = \csc \theta $ so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{1}{{\cos \theta \times \sin \theta }} + 1 = \sec \theta \times \csc \theta + 1\]
= R.H.S
Hence proved
Note – Whenever we face such types of questions the key point is simply to have a good grasp over the trigonometric identities, some of them have been mentioned above while performing the solution. Start by simplifying any one side and application of these identities along with some algebraic identities will help you reach the right answer.
Complete step by step solution:
Given equation is
$\dfrac{{\tan \theta }}{{\left( {1 - \cot \theta } \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}} = 1 + \tan \theta + \cot \theta = \sec \theta \times \csc \theta + 1$
Consider L.H.S
$ \Rightarrow \dfrac{{\tan \theta }}{{\left( {1 - \cot \theta } \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}$
Now as we know \[\cot \theta = \dfrac{1}{{\tan \theta }}\] so, substitute this value in above equation we have,
\[\dfrac{{\tan \theta }}{{\left( {1 - \dfrac{1}{{\tan \theta }}} \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}\]
Now simplify the above equation we have,
\[ \Rightarrow \dfrac{{{{\tan }^2}\theta }}{{\left( {\tan \theta - 1} \right)}} + \dfrac{{\cot \theta }}{{\left( {1 - \tan \theta } \right)}}\]
\[ \Rightarrow \dfrac{{{{\tan }^2}\theta }}{{\left( {\tan \theta - 1} \right)}} - \dfrac{{\cot \theta }}{{\left( {\tan \theta - 1} \right)}} = \dfrac{{{{\tan }^2}\theta - \dfrac{1}{{\tan \theta }}}}{{\tan \theta - 1}} = \dfrac{{{{\tan }^3}\theta - 1}}{{\tan \theta \left( {\tan \theta - 1} \right)}}\]
Now as we know $\left( {{a^3} - {b^3}} \right) = \left( {a - b} \right)\left( {{a^2} + {b^2} + ab} \right)$ so, use this property in above equation we have,
\[ \Rightarrow \dfrac{{\left( {\tan \theta - 1} \right)\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta \left( {\tan \theta - 1} \right)}} = \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }}\]
Now divide by $\tan \theta $ in above equation we have,
\[ \Rightarrow \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }} = 1 + \tan \theta + \cot \theta \]
= R.H.S
Now we have to again prove that
$1 + \tan \theta + \cot \theta = \sec \theta \times \csc \theta + 1$
Now consider L.H.S
\[ \Rightarrow 1 + \tan \theta + \cot \theta \]
\[ \Rightarrow 1 + \tan \theta + \cot \theta = \dfrac{{\left( {{{\tan }^2}\theta + 1 + \tan \theta } \right)}}{{\tan \theta }}\] (From above equation)
Now as we know that \[\left[ {{\text{ta}}{{\text{n}}^2}\theta + 1 = {{\sec }^2}\theta } \right]\] so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{{{{\sec }^2}\theta + \tan \theta }}{{\tan \theta }} = \dfrac{{{{\sec }^2}\theta }}{{\tan \theta }} + 1\]
Now we know that \[{\text{sec}}\theta {\text{ = }}\dfrac{1}{{\cos \theta }},{\text{ }}\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}\] so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{{{{\sec }^2}\theta }}{{\tan \theta }} + 1 = \dfrac{{\cos \theta }}{{{{\cos }^2}\theta \times \sin \theta }} + 1 = \dfrac{1}{{\cos \theta \times \sin \theta }} + 1\]
Now we know $\dfrac{1}{{\sin \theta }} = \csc \theta $ so, substitute this value in above equation we have,
\[ \Rightarrow \dfrac{1}{{\cos \theta \times \sin \theta }} + 1 = \sec \theta \times \csc \theta + 1\]
= R.H.S
Hence proved
Note – Whenever we face such types of questions the key point is simply to have a good grasp over the trigonometric identities, some of them have been mentioned above while performing the solution. Start by simplifying any one side and application of these identities along with some algebraic identities will help you reach the right answer.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE